PERANCANGAN COVER DIGIPAK ALBUM FISIK ”SEJAK TAK LAGI BERSAMA” KARYA GUNSALEH BERBASIS AUGMENTED REALITY - Rasi, Valentina; Bakti, Amar Ma'ruf Stya; Pramudya, Bintang (Ma Chung Press, Universitas Ma Chung, 2025)
The advancement of technology today has driven a significant transformation in the music industry, particularly for independent musicians. One of the challenges faced is the declining interest in physical albums due to the dominance of streaming platforms. This final project aims to create an innovative visual solution by designing a physical album integrated with Augmented Reality (AR), focusing on the album